Low Serum Levels of DKK2 Predict Incident Low‐Impact Fracture in Older Women. (28th March 2019) - Rodrigues, Ana M; Eusébio, Mónica; Rodrigues, Ana B; Caetano‐Lopes, Joana; Lopes, Inês P; Lopes, Ana; Mendes, Jorge M; Coelho, Pedro Simões; Fonseca, João Eurico; Branco, Jaime C; Canhão, Helena
Abstract: There are currently no robust noninvasive markers of fragility fractures. Secreted frizzled related protein‐1 (sFRP‐1), dickkopf‐related protein 1 (DKK1) and DKK2, and sclerostin (SOST) inhibit Wnt signaling and interfere with osteoblast‐mediated bone formation. We evaluated associations of serum levels of sFRP‐1, DKK1, DKK2, and SOST with incident low‐impact fracture and BMD in 828 women aged ≥65 years from EpiDoC, a longitudinal population‐based cohort. A structured questionnaire during a baseline clinical appointment assessed prevalent fragility fractures and clinical risk factors (CRFs) for fracture. Blood was collected to measure serum levels of bone turnover markers and Wnt regulators. Lumbar spine and hip BMD were determined by DXA scanning. Follow‐up assessment was performed through a phone interview; incident fragility fracture was defined by any new self‐reported low‐impact fracture. Multivariate Cox proportional hazard models were used to analyze fracture risk adjusted for CRFs and BMD. During a mean follow‐up of 2.3 ± 1.0 years, 62 low‐impact fractures were sustained in 58 women. A low serum DKK2 level (per 1 SD decrease) was associated with a 1.5‐fold increase in fracture risk independently of BMD and CRFs. Women in the two lowest DKK2 quartiles had a fracture incidence rate of 32 per 1000 person‐years, whereas women in the two highest quartiles had 14 fragility fractures per 1000 person‐years. A high serum sFRP1 level was associated with a 1.6‐fold increase in fracture risk adjusted for CRFs, but not independently of BMD. Serum levels of SOST ( r = 0.191; p = 0.0025) and DKK1( r = −0.1725; p = 0.011) were correlated with hip BMD, but not with incident fragility fracture. These results indicate that serum DKK2 and sFRP1 may predict low‐impact fracture. The low number of incident fractures recorded is a limitation and serum levels of Wnt regulators should be further studied in other populations as potential noninvasive markers of fragility fractures. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.